Adolescent-to-Parent Violence: Psychological and Family Adjustment - Seijo, Dolores; Vázquez, María J.; Gallego, Raquel; Gancedo, Yurena; Novo, Mercedes (Frontiers in Psychology, 2020)
Adolescent-to-Parent Violence (APV) or Child-to-Parent Violence (CPV) is a specific form of violence that has remained inconspicuous until recently, but is becoming a mounting social issue and is increasingly the focus of scientific research. Of the variables related to APV, the study assessed the characteristics of the family system and its relationship to the psychosocial adjustment of adolescents, an aspect scarcely examined in the literature. Thus, a field study was performed on a community sample of 210 adolescents aged 12 to 17 years (51.4% girls) who were assessed on measurements of APV, parenting (parental socialization), victimization, and psychological adjustment (personal, family, and school). The results revealed higher rates of psychological APV, and no gender effects in violence exercised against either parent. The adolescents involved in APV, exhibited greater psychological maladjustment in the different areas under analysis. Moreover, adolescents engaging in psychological APV reported a parental socialization style characterized by severe strictness and supervision in comparison to non-aggressors not implicated in psychological APV. Finally, adolescents exercising APV, who were victimized by their parents showed more psychological, personal, and school maladjustment. These results have implications for needs analysis, and the planning of community prevention strategies.